2019
DOI: 10.1111/hdi.12771
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent pneumatic compression in patients with ESRD. A systematic review

Abstract: Introduction: Patients with end‐stage renal disease (ESRD) experience frequent hemodialysis (HD) complications. Intradialytic hypotension (IDH) is a common complication presenting in approximately between 20 and 50% of HD sessions. Available interventions such as volume replacement or vasoactive medications are associated with significant side effects. Intermittent pneumatic compression (IPC) has been proposed as a feasible intervention for the prevention of IDH, treatment of peripheral arterial disease and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The use of compression stockings in patients with renal dysfunction was well-tolerated 79 but with different hemodynamic outcomes if renal failure is present. Also, pneumatic compression was found to be useful 80 and associated with good tolerance, with a positive impact on, for example, DIH (Dialysis-Induced Hypotension). Pneumatic compression during the first hour of dialysis was associated with less DIH with no effect on fluid parameters.…”
Section: With No Evidence But Also With No Risk—looking For a Solutionmentioning
confidence: 99%
“…The use of compression stockings in patients with renal dysfunction was well-tolerated 79 but with different hemodynamic outcomes if renal failure is present. Also, pneumatic compression was found to be useful 80 and associated with good tolerance, with a positive impact on, for example, DIH (Dialysis-Induced Hypotension). Pneumatic compression during the first hour of dialysis was associated with less DIH with no effect on fluid parameters.…”
Section: With No Evidence But Also With No Risk—looking For a Solutionmentioning
confidence: 99%
“…Unfortunately, there is no RCT data on the effect of increasing physical activity levels and the association with mortality in the haemodialysis population. Although, as recommended by the most recent Kidney Disease Improving Global Outcomes (KDIGO) guidelines [ 88 ] and the UK Chief Medical Officers’ Guideline [ 89 ] increasing physical activity levels should be encouraged (aiming for at least 30 min of moderate intensity activity, 5 times per week). It is also important to highlight that even small increases in physical activity levels is likely to provide some benefit.…”
Section: Haemodialysismentioning
confidence: 99%
“…We read with unadulterated excitement, the recent systematic review by Torres et al assessing the efficacy and safety of intermittent pneumatic compression (IPC) in the management of intradialytic hypotension (IDH) in patients with ESRD undergoing hemodialysis . We were the first to report on the application of the principle of enhanced external counter pulsation (EECP) in this regard .…”
mentioning
confidence: 99%
“…This systematic review concluded that IPC might offer significant benefits for patients undergoing hemodialysis not limited to prevention of IDH but also improvement of hemodialysis comfort and physical capacity …”
mentioning
confidence: 99%